AL HASAN ISLAMIC BOARDING SCHOOL'S STRATEGY FOR DEVELOPING A CADRE OF ISLAMIC PROPAGATION IN BEKASI CITY - Sukroni, Abdul (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2026)
Abstract: This article discusses the strategy of the modern Islamic boarding school Al Hassan Bekasi City in forming da'wah cadres who are adaptive and responsive to contemporary da'wah developments. Using a qualitative approach with analytical descriptive methods, this study collected primary data from the Modern Islamic Boarding School Al Hassan. The results show that the Modern Islamic Boarding School Al Hassan's strategy in forming da'wah cadres is through an integrated educational process, combining religious and general curriculum, emphasizing the strengthening of faith, character, da'wah skills, Qur'an memorization, sharia knowledge, the use of digital media and entrepreneurship. Challenges faced include material imbalances, technological limitations, and minimal external partnerships.